Formation of the transition zone “matrix alloy – reinforcing granules” in the process of solid‑liquid synthesis of composite material - A. S. Kalinichenko; V. A. Kalinichenko; V. G. Luhin (Литьë и металлургия)
The paper is devoted to the formation of transition zone between matrix alloy and reinforcing phase (cast iron granules) during the synthesis of composite casted materials. Results on concentration distribution of main elements (Si, Fe, Cu) are presented. It is shown that the formation of transition zone starts during the infiltration process with further its growth during the exposition at synthesis temperature. As the result dissolution and distraction of granules take place.